Determinants of Islamic commercial banks financing risk in Indonesia - Sari, Mella Katrina (Journal of Islamic Economics Lariba, 2016)
This research is aimed to show the empirical evidence of the influence of Financing Expansion, Financing Quality, Financing to Deposit Ratio, and Return on Assets on financing risk in Islamic Commercial Banks in Indonesia. This research uses purposive sampling so that three Islamic Commercial Banks are choosen: Bank Syariah Mandiri, Bank Muamalat Indonesia, and Bank Mega Syariah Indonesia. The analysis method of this research is panel data regression analysis. This research applies Panel Unit Roots (PRUTS), model specification test using Fixed Effect Model, classical assumption test (Homoscedastic, Autocorrelation, and Prais-Winsten Regression), hypothesis testing with a significance level of 5%. The result shows that Financing Expansion and Return on Assets have a negative and significant influence on financing risk. Meanwhile, Financing Quality and Financing to Deposit Ratio have a positive and significant influence on financing risk.